Experiences with Point-Mass Gravity Field Modelling in the Perth Region, Western Australia - Claessens, Sten; Featherstone, Will (Institution of Surveyors, Australia, 2001)
Gravimetric geoid modelling in the Perth region of Western Australia has attracted much attention in recent years because of the numerous restrictions in this area, such as the presence of the Darling Fault system and variable gravity data coverage and quality. This paper presents the results of experiments to determine the effectiveness of free-positioned point-mass modelling in relation to the previous attempts based on Stokes's integral. It is shown that the point-mass modelling technique does not yield improved fits to 99 local GPS-levelling data with a standard deviation of the fit of +/- 17.5cm. However, the experiments do show that the technique is a useful tool for conveniently identifying areas where there are large topographic mass density contrasts and mismatches among the gravity data used. Therefore, the technique, though apparently not optimal for geoid modelling in this region at this point in time, may provide a useful indicator of problems that will affect geoid omputations using other techniques.